Residual counter ions can stabilise a large protein complex in the gas phase - Freeke, J; Robinson, C; Ruotolo, B (2010)
The dual goals of retaining native solution structure in the gas phase and facilitating accurate mass measurement by mass spectrometry often require conflicting experimental parameters. Here, we use ion mobility-mass spectrometry to investigate the effects of aqueous buffer removal on the structure of an archetypal ring complex, GroEL, an 800. kDa chaperone protein complex from Escherichia coli. Our data show that subjecting the protein complex ions to energetic collisions in the gas phase removes aqueous buffer from the assembly in a manner indicative of at least two populations of adducts bound to the complex. Adding further energy to the system disrupts the quaternary structure of the assembly, causes monomer unfolding, and eventual dissociation at higher collision energies. Including additional salts of lower volatility in a typical ammonium acetate buffer produces gas-phase protein complex ions that are seemingly stabilised relative to changes in gas-phase structure. These data are combined to offer a general picture of the desolvation and structural transitions undergone by large gas-phase protein complexes. © 2009 Elsevier B.V.